Bacterial Communities in Concrete Reflect Its Composite Nature and Change with Weathering - E. Anders Kiledal (American Society for Microbiology, 2021)
Concrete is the most-used building material in the world and a biologically extreme environment, with a microbiome composed of bacteria that likely come from concrete precursor materials, aerosols, and environmental deposition. These microbes, though seeded from a variety of materials, are all subject to desiccation, heating, starvation, high salinity, and very high pH.